2000
DOI: 10.1002/1099-1026(200007/08)15:4<281::aid-ffj916>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Sesquiterpene hydrocarbons of cold-pressed lime oils

Abstract: The sesquiterpene hydrocarbon composition of cold‐pressed lime oils of the Key lime (type A and B) and the Persian lime varieties were investigated. α‐Santalene, γ‐curcumene, β‐selinene, β‐sesquiphellandrene and 7‐epi‐α‐selinene were confirmed as so far unknown trace constituents of cold‐pressed lime oils. The usage of unusually gentle GC conditions permitted the establishment of germacrenes A and C, both thermally and chemically sensitive compounds, as important constituents of cold‐pressed lime oil for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Peel: essential oil (sesquiterpene hydrocarbons [␣-santalene, ␥-curcumene, ␤-selinene and germacrenes A, B, C, D], monoterpene hydrocarbons (sabinene, ␥-pinene, limonene), monoterpene alcohols (linalool, terpinen-4-ol, ␣-terpineol), ␥-terpinene, esters, monoterpene aldehydes, aliphatic aldehydes, pectinesterase (Syamsuhidayat and Hutapea, 1991;Dugo et al, 1997;Limyati and Juniar, 1998;Mondello et al, 1998;Contreras-Esquivel et al, 1999;Feger et al, 2000). Pulp: sucrose, protein components (Echeverría, 1992;Gharagozloo and Ghaderi, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Peel: essential oil (sesquiterpene hydrocarbons [␣-santalene, ␥-curcumene, ␤-selinene and germacrenes A, B, C, D], monoterpene hydrocarbons (sabinene, ␥-pinene, limonene), monoterpene alcohols (linalool, terpinen-4-ol, ␣-terpineol), ␥-terpinene, esters, monoterpene aldehydes, aliphatic aldehydes, pectinesterase (Syamsuhidayat and Hutapea, 1991;Dugo et al, 1997;Limyati and Juniar, 1998;Mondello et al, 1998;Contreras-Esquivel et al, 1999;Feger et al, 2000). Pulp: sucrose, protein components (Echeverría, 1992;Gharagozloo and Ghaderi, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…These compounds seem to form a small subgroup that characterizes these three species, although some of them may sporadically be found in other Citrus common species, such as C. medica . This is the case of the previously named α-bisabolol, and also of ( E )-α-bisabolene, which has been very frequently isolated in C. limon (Verzera et al, 2001; Lota et al, 2002; Liu et al, 2012; Spadaro et al, 2012; Blázquez and Carbó, 2015; Cannon et al, 2015; Petretto et al, 2016), in C. aurantifolia (Feger et al, 2000; Craske et al, 2005; Costa et al, 2014) and occasionally in C. paradisi (Flamini and Cioni, 2010), C. medica (Lota et al, 1999) and C. bergamia (Costa et al, 2010); ( Z )-α-bisabolene, very frequently isolated in C. limon (Verzera et al, 2001; Ferhat et al, 2007; Spadaro et al, 2012; Blázquez and Carbó, 2015; Cannon et al, 2015; Zhang et al, 2017) and C. bergamia (Verzera et al, 2003; Cosimi et al, 2009; Costa et al, 2010), and occasionally in C. aurantifolia (Feger et al, 2000; Zhang et al, 2017), C. medica (Verzera et al, 2005), and C. aurantium (Lota et al, 2001a); γ-curcumene, frequently reported in C. limon (Ferhat et al, 2007; Blázquez and Carbó, 2015; Cannon et al, 2015; Petretto et al, 2016), C. bergamia (Costa et al, 2010) and C. aurantifolia (Feger et al, 2000; Costa et al, 2014); β-santalene, isolated mainly in C. limon (Spadaro et al, 2012; Blázquez and Carbó, 2015; Cannon et al, 2015; Petretto et al, 2016), C. bergamia (Verzera et al, 2003; Cosimi et al, 2009; Costa et al, 2010; Furneri et al, 2012), and C. aurantifolia (Feger et al, 2000; Minh Tu et al, 2002a; Costa et al, 2014; Zhang et al, 2017); and campherenol, reported mainly in C. limon (Verzera et al, 2004; Spadaro et al, 2012; Cannon et al, 2015) and C. bergamia (Mondello et al, 2003; Verzera et al, 2003; Costa et al, 2010; Furneri et al, 2012), and sporadically in C. aurantifolia (Dugo and Mondello, 2011) and C. medica (Lamine et al, 2018). Unfortunately, the identification of most of these sesquiterpenes is not totally reliable, since it seems that standards of t...…”
Section: Volatile Compounds Identified In Essential Oils From Peel Lmentioning
confidence: 92%
“…Despite the distance with C. limon , there are some terpene compounds which have been exclusively reported in C. aurantifolia and C. limon , such as the monoterpene geranic oxide [ C. aurantifolia (Chisholm et al, 2003b) and C. limon (Cannon et al, 2015)]. Interestingly, the monoterpenoid isogeranial and the sesquiterpene α-santalene have been described only in C. aurantifolia (Feger et al, 2000; Costa et al, 2014), C. medica (Venturini et al, 2014; Mitropoulou et al, 2017) and C. limon (Vekiari et al, 2002; Cannon et al, 2015).…”
Section: Volatile Compounds Identified In Essential Oils From Peel Lmentioning
confidence: 99%
“…After, the oil is recuperated through centrifugation. Such a process is applied to both Key (type B oil) and Persian limes [1].…”
Section: Introductionmentioning
confidence: 99%